Effectiveness and tolerability of the combined use of anti-VEGF agents in clinical practice - A.V. Kuroyedov; O.V. Gapon’ko; V.V. Gorodnichiy; S.V. Diordiychuk; I.V. Kondrakova; N.M. Sol’nov; N.E. Fomin (РМЖ "Клиническая офтальмология")
A.V. Kuroyedov1,2, O.V. Gapon’ko1,2, V.V. Gorodnichiy1, S.V. Diordiychuk1, I.V. Kondrakova1, N.M. Sol’nov1, N.E. Fomin1,2 1P.V. Mandryka Military Clinical Hospital, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation Aim: to assess the effectiveness and tolerability of anti-VEGF agents, aflibercept (2.0 mg) and ranibizumab (0.5 mg), in the combined treatment for wet age-related macular degeneration (AMD) in routine clinical practice. Patients and Methods: 55 patients (65 eyes) with the late stage of wet AMD were divided into two groups. Group 1 included 32 eyes with classic choroidal neovascularization (CNV) and group 2 included 33 eyes with occult CNV. Best-corrected visual acuity (BCVA), intraocular pressure, and retinal nerve fiber layer (RNFL) thickness were measured. These parameters were compared at different time points during the treatment. Results: overall AMD duration (January 2019) was 36 (19; 47) months being 30 (12; 44) months in group 1 and 36 (23; 48) months in group 2 (р>0.05). The first intravitreal administration of an anti-VEGF drug was performed 7.5 (3.5; 9.5) months after AMD diagnosis in group 1 and 7 (3; 11) months after AMD diagnosis in group 2. Significant differences in intragroup intervals were revealed between various follow-up periods. More differences were identified for the intervals between intravitreal administrations in group 2. Baseline and final BCVA during the entire follow-up which was 29.5 (19.5; 38) months in group 1 and 28 (25; 44) months in group 2 demonstrated neither intragroup nor intergroup differences (р>0.05). Conclusion: our management strategy for wet AMD is somewhat different from conventional guidelines. However, it has no significant impact on visual acuity during the follow-up. Keywords: age-related macular degeneration, anti-VEGF drugs, intravitreal administration, IOP level, aflibercept, ranibizumab. For citation: Kuroyedov A.V., Gapon’ko O.V., Gorodnichiy V.V. et al. Effectiveness and tolerability of the combined use of anti-VEGF agents in clinical practice. Russian Journal of Clinical Ophthalmology. 2020;20(4):209–215. DOI: 10.32364/2311-7729-2020-20-4-209-215.